La proporcionalidad de la pena en el delito de sicariato cometido por adolescentes infractores. - Tenelema Estrada, Byron Fabian (2024)
ABSTRACT The present investigation entitled “THE PROPORTIONALITY OF THE PENALTY IN THE CRIME OF HARDMEN COMMITTED BY ADOLESCENT OFFENDERS” has been developed in view of the increase in adolescents participating in criminal acts of hitman at present, which is why the purpose of the study was to investigate what the specific penalty would be when judging a teenager for committing the crime of hitman. A bibliographic research was carried out at a scientific and legal level that allowed the study variables to be characterized. Within the methodology, a type of basic, documentary, bibliographic, legal-descriptive and historical descriptive research was used, the design was non-experimental, the evaluation instruments were the survey and the interview, which was applied to lawyers in free practice. and to the Judges of the criminal court and Judges of the Violence against Women Unit and Members of the Family Nucleus. Through the analysis and discussion of the results, it was possible to verify the hypothesis, which refers to the fact that proportionality does affect the punishment in the crime of contract killing committed by adolescent offenders. It can be concluded that legally and doctrinally, there has been a need to increase the penalty for adolescents who commit the crime of hitmen, this is due to the fact that these people are aware of the crime they are going to commit. Keywords: Principle of proportionality – Crimes – Hiring – Hiring in adolescents.